Pengetahuan Masyarakat Lokal Di Kawasan Penyangga Cagar Alam Hutan Bakau Pantai Timur Resort Mendahara Provinsi Jambi Terhadap Pemanfaatan Keanekaragaman Hayati Mangrove - Wulandari, Tia; Suprayogi, Dawam; Ihsan, Mahya; Aulia Putri, Tazkiah (Jurnal Pendidikan Biologi Undiksha, 2025)
The utilization of organism in the mangrove forest area should always in minimum tolerance of utilization, especially in the vicinity of conservation areas. Therefore, as an initial step to assess the knowledge and understanding of community in the buffer village of the East Coast Mangrove Forest Conservation Area (CAHBPT) need to be conducted. The research was carried out from April to September 2023. This research is descriptive research which divided in two steps, namely interviews with respondents and sample identification. The interview method used in this research is semi-structured interviews, which open-ended and conducted on topic development. Respondent selection in this research uses the snowball sampling technique (26 respondents which conducted by 16 males and 10 females). The result shows the knowledge and understanding of community in the buffer village of the East Coast Mangrove Forest Conservation Area (CAHBPT) about the important of conservation activity is relatively high. 90% of the respondents are familiar with the term of CAHBPT and the conservation efforts being undertaken. The involvement of the BKSDA Jambi has a significant impact of the knowledge and understanding of the community.